Insights into Brevibacillus borstelensis AK1 through Whole Genome Sequencing: A Thermophilic Bacterium Isolated from a Hot Spring in Saudi Arabia. (24th May 2018) - Khalil, Amjad B.; Sivakumar, Neelamegam; Arslan, Muhammad; Saleem, Hamna; Qarawi, Sami
Abstract : Brevibacillus borstelensis AK1 is a thermophile which grows between the temperatures of 45°C and 70°C. The present study is an extended genome report of B. borstelensis AK1 along with the morphological characterization. The strain is isolated from a hot spring in Saudi Arabia (southeast of the city Gazan). It is observed that the strain AK1 is rod-shaped, motile, and strictly aerobic bacterium. The whole genome sequence resulted in 29 contigs with a total length of 5, 155, 092 bp. In total, 3, 946 protein-coding genes and 139 RNA genes were identified. Comparison with the previously submitted strains of B. borstelensis strains illustrates that strain AK1 has a small genome size but high GC content. The strain possesses putative genes for degradation of a wide range of substrates including polyethylene (plastic) and long-chain hydrocarbons. These genomic features may be useful for future environmental/biotechnological applications.